Dichotomies, Canons, and Queer Perspectives in Galician Literature - Regueira, Mario (Madrygal. Revista de Estudios Gallegos, 2026)
The issues discussed in this article address the role, trajectory, and challenges of queer studies in relation to Galician culture and literature, understood as part of a peripheral reality undergoing a process of emergence. The analysis examines general methodological aspects that have shaped the development of the idea of the canon within queer studies and contrasts them with certain strategies and specific cases in the history of Galician literature, paying particular attention to the difficulties of articulation posed by some of its classical assumptions. At the same time, the article assesses the role of documentation and the biographical trace of authorial voices, considering the compensatory function between an idealized objectivity that inhibits structural critique and the legitimate role of subjectivity in research. In this regard, it also gives room to the perspectives opened by textual hermeneutics and to the potential role of interpretation, suspicion, and informal knowledge.